A sisa, primeiro imposto geral e permanente em Portugal e as tensões de uma sociedade pouco conhecida - Leonor García da Cruz, Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Study on the tensions in 16th century Portuguese society, concerning “sisa” (excise tax), mainly on the Jewish descent of tax agents (central, regional and local administrations) and the plural views on them, either as “executioners” or as “victims”. In the Treasury and Imagetics Studies Programme at the History Centre of FLUL and Seminar “Economy and Society in Modern Period” (Faculty of Arts of the University of Lisbon, MA and PhD)